A posteriori modality, implicative modality by abduction. A case study: he must have been drunk to have said that - Geneviève Girard-Gillet (Anglophonia)
The construction “he must have been drunk to have said that” has not been analysed in depth, even if it has been mentioned by P. Larreya, G. Furmaniak, E. Gilbert, among other linguists working on modalisation. It is particular in that it expresses, with an infinitival proposition, an event that took place before Speech Time, and, with a modalized proposition, the cause that, according to the speaker, can explain the occurrence. We are enlarging here the concept of a posteriori modalization, defined by Larreya (2000, 2009), to include cases in which the event that triggers the modal stance of the speaker is explicitly mentioned and not presupposed. This construction is highly constrained as it requires the presence of an epistemic modal form. It differs from constructions that have been more consistently studied, such as “John was stupid to refuse the job” (Stowell, Kertz, Desurmont). It is the nature of the cause-consequence link that enables one to construe a possible interpretation, and we consider that the inference is made by abduction (Pierce 1974, Desclés 2000). This explains that it is rare and highly expressive, since an abductive inference only yields plausible conclusions, which the speaker must ascertain as its own. The construction functions as a whole (syntactically, semantically, phonologically) and builds up its own interpretation, through the reconciliation of jarring viewpoints by the speaker. It expresses some kind of humour, irony even, and always denotes the speaker’s astonishment at what happened and at the reason why a particular individual took part in the event in question.